Makna Perjanjian Pernikahan Kristen dan Implikasinya Terhadap Transformasi Budaya Pernikahan Adat Sumba di Lingkungan Gereja Bethel Indonesia Waikabubak - Angeline Roesdiyono; Sjanette Eveline; Juanda Juanda (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2026)
This study aims to examine the theological concept of the marriage covenant in the Christian faith based on the Bible and its relevance to Sumbanese traditional wedding practices. The marriage covenant in Christianity is understood as a sacred bond that reflects the relationship between Christ and His congregation. This study aims to understand the theological and spiritual foundations of the Christian marriage covenant and assess how these principles can be integrated or interact with Sumbanese traditional wedding practices within the local cultural context. This study uses a qualitative approach with a case study method, involving five key informants: a pastor, a council member, two Christian couples married in traditional and church marriages, and one Christian couple about to marry. This approach allows for in-depth exploration of their experiences, understandings, and perspectives on the meaning of the marriage covenant from both perspectives. The results of this study indicate that the marriage covenant in the Christian faith emphasizes the dimensions of sacredness, fidelity, and mutual responsibility between husband and wife as a reflection of Christ’s love for His congregation. On the other hand, Sumbanese traditional weddings are rich in cultural symbols that bind two extended families, but do not fully embody Christian spiritual values. Therefore, cultural transformation through a theological approach is essential to ensure that traditional wedding practices do not conflict with the values of the Christian faith. This research contributes to Christian families, churches, and indigenous communities in building a more integrative understanding between God’s word and local cultural richness.